Bioactivation of lumiracoxib in human liver microsomes: Formation of GSH‐ and amino adducts through acyl glucuronide. Issue 6 (19th February 2020) - Jiao, Weijie; Zhao, Xu; Wu, Guiyue; Zhang, Xiangyun; Wu, Hong; Cui, Yinglin
Abstract: Lumiracoxib is a selective cyclooxygenase‐2 inhibitor, which has been reported to cause rare but severe liver injury. Considering that lumiracoxib has a carboxylic group in the molecule, glucuronidation to form acylglucuronide would be one of the possible mechanisms of lumiracoxib‐induced liver injury. The aim of this study was to identify the metabolites of lumiracoxib that were formed via acyl‐glucuronidation in human liver microsomes using glutathione (GSH) and N ‐acetyl‐lysine (NAL) as trapping agents by liquid chromatography combined with high resolution mass spectrometry. The structures of the detected metabolites were identified by their accurate masses, fragment ions, and retention times. Under the current conditions, eight lumiracoxib associated metabolites were identified. With the presence of UDPGA, lumiracoxib was biotransformed into lumiracoxib‐1‐O‐acylglucuronide (M1) and 4′‐hydroxyl‐lumiracoxib‐1‐O‐acylglucuronide (M2), both of which were reactive and prone to react with GSH to form drug‐S‐acyl‐GSH adducts (M3 and M4) through transacylation. In addition to reaction with GSH, the formed 1‐O‐acylglucuronides were chemically unstable (T1/2 = 1.5 h in phosphate buffer) and rearranged to 2‐, 3‐, and/or 4‐isomers, which further underwent ring‐opening to form aldehyde derivatives and then reacted with NAL to yield Schiff base derivatives (M5–M8). The present study provides a clear bioactivation profile of lumiracoxib through acyl glucuronidation, which would be one of the mechanisms attributed to liver injury caused by lumiracoxib. Abstract : Lumiracoxib is a COX‐2 inhibitor, which was withdrawn from the market due to the rare but severe hepatotoxicity. In this study, new bioactivation pathways through acyl‐glucuronidation were disclosed. The present study provides a clear bioactivation profiles of lumiracoxib through acyl‐glucuronidation, which would be one of the mechanisms attributed to the liver injury caused by lumiracoxib.